Fecal microbial characterization of hospitalized patients with suspected infectious diarrhea shows significant dysbiosis - Tzipi Braun (Nature Portfolio, 2017)
Abstract Hospitalized patients are at increased risk for acquiring healthcare-associated infections (HAIs) and inadequate nutrition. The human intestinal microbiota plays vital functions in nutrient supply and protection from pathogens, yet characterization of the microbiota of hospitalized patients is lacking. We used 16S rRNA amplicon sequencing to characterize the global pattern of microbial composition of fecal samples from 196 hospitalized patients with suspected infectious diarrhea in comparison to healthy, non-hospitalized subjects (n = 881), and to traditional culture results. We show that hospitalized patients have a significant rise in α-diversity (richness within sample) from birth to <4 years of age, which continues up to the second decade of life. Additionally, we noted a profoundly significant increase in taxa from Proteobacteria phylum in comparison to healthy subjects. Finally, although more than 60% of hospitalized samples had a greater than 10% abundance of Proteobacteria, there were only 19/196 (10%) positive cultures for Campylobacter, Salmonella, or Shigella entero-pathogens in traditional culturing methods. As hospitalized patients have increased risk for HAIs and inadequate nutrition, our data support the consideration of nutritional and/or microbial modification in this population.